COMPARISON OF TRANSTHORACIC AND TRANS-ESOPHAGEAL ECHOCARDIOGRAPHY IN THE DETECTION OF CARDIAC EMBOLI IN AFIB PATIENTS - PASHA , H; SUBHAN , U; SALIM , M (Biological and Clinical Sciences Research Journal, 2024)
Atrial fibrillation (AFib) predisposes patients to an increased risk of thromboembolic events, including stroke, due to the formation of cardiac emboli. Transthoracic echocardiography (TTE) and transoesophageal echocardiography (TEE) are commonly used to detect cardiac emboli in AFib patients, but their comparative effectiveness remains unclear. Objective: This study aimed to compare the diagnostic accuracy of TTE and TEE in detecting cardiac emboli in AFib patients. Methods: A prospective observational study was conducted at the Shifa International Hospital in Islamabad, Pakistan, from January 2022 to January 2023. The study included 100 adult patients diagnosed with AFib, undergoing evaluation for suspected cardiac emboli. Both TTE and TEE examinations were performed as part of routine clinical care. Diagnostic accuracy parameters were calculated for both modalities using standard formulas, and comparative analyses were conducted using appropriate statistical tests. SPSS version 25 was used, and a P value less than 0.05 is considered statistically significant. Results: The study included 100 patients with atrial fibrillation (AFib), of which 55 were male, and 45 were female. The mean age of the patients was 65 years (standard deviation [SD] ± 7 years). Transoesophageal echocardiography (TEE) demonstrated a higher sensitivity in detecting cardiac emboli than transthoracic echocardiography (TTE). TEE identified a significantly higher number of emboli than TTE (48 vs. 40, p < 0.05). TEE was also associated with a lower risk of complications than TTE (0 vs. 2 cases, p < 0.05). Conclusion: In evaluating cardiac emboli in AFib patients, transoesophageal echocardiography (TEE) showed superior diagnostic accuracy and a lower complication risk than transthoracic echocardiography (TTE). Therefore, TEE may be considered the preferred imaging modality for this patient population.